Ranfurly Library Service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The Ranfurly Library Service is a book aid charity based in the UK which distributes over 650,000 books every year in response to requests from more than 60 developing countries around the world. The books are sent to educational and community...